Integrating Community-based Research into a Senior Capstone Seminar: Lessons from a Mixed-method Study - Shostak, Sara; Corral, Margarita; Ward, Ann (TRAILS: Teaching Resources and Innovations Library for Sociology, 2020)
This article describes a senior capstone, Neighborhoods and Health, which used community-based research (CBR) as its primary pedagogy. Students in the course drew upon multiple research methods and forms of data to provide our partner, the Urban Farming Institute of Boston, with an array of research products in support of the revitalization of a historic farm in the Boston neighborhood of Mattapan. Based on pre- and posttest assessment and analysis of students’ reflections in their journals, we identify how a multimethods approach—combined with a commitment to producing usable research products—simultaneously contributed to students’ research methods proficiency and their understanding of complex social processes. For both sociology departments and interdisciplinary majors that draw on sociological perspectives, CBR offers a compelling means of providing seniors with meaningful capstone experiences while adding capacity to the important work of community-based organizations.